Pengelolaan Data Sampah Pada Bank Sampah Kita (Basuki) Semarang Berbasis Aplikasi MS Excel - Setyawan Wibisono; Wiwien Hadikurniawati; Imam Husni Al Amin; Taufiq Dwi Cahyono (Intimas, 2023)
Based on surveys and discussions in the field with the manager of the "Basuki" Garbage Bank, RT 02, RW 08 Sinar Waluyo Housing, Kedungmundu Village, Semarang, it can be seen that partner problems: 1) Joint management of the "Basuki" Garbage Bank is still relatively short, so the management who new managers must learn from scratch in waste management: 2) In the operational activities of the "Basuki" Garbage Bank, new managers must memorize the many types of waste and the unit price of waste that is worth selling: 3) In recording the entry and exit of waste data, there is no standard and standard format , because it is still in the learning stage; 4) Members cannot see waste management data directly, because waste management data is only recorded in a notebook. To realize community service in training at the "Basuki" Garbage Bank the method applied is a participatory action review which is implemented through training with the following stages: 1) Basic waste bank data recording training using a standard waste bank format; 2) Software training for recording waste bank data; 3) Software training for preparing waste bank reports.